Lithium production in the merging of white dwarf stars - Longland, Richard (2012)
The origin of R Coronae Borealis stars has been elusive for over 200 years. Currently, two theories for their formation have been presented. These are the final flash scenario, in which a dying asymptotic giant branch star throws off its atmosphere to reveal the hydrogen poor, heavily processed material underneath, and the double degenerate scenario, in which two white dwarfs merge to produce a new star with renewed vigour. Some theories predict that the temperatures reached during the latter scenario would destroy any lithium originally present in the white dwarfs. The observed lithium content of some R Coronae Borealis stars, therefore, is often interpreted as an indication that the final flash scenario best describes their formation. In this paper, we show that lithium production can, indeed, occur in the merging of a helium white dwarf with a carbon-oxygen white dwarf if their chemical composition, particularly that of 3He, is fully considered. The production mechanism is described in detail, and the sensitivity of lithium production to the merger environment is investigated. Nucleosynthesis post-processing calculations of smoothed-particle hydrodynamics (SPH) tracer particles are performed to show that any lithium produced in these environments will be concentrated towards the cloud of material surrounding the R CrB star. Measurements of the lithium content of these clouds would, therefore, provide a valuable insight into the formation mechanism of R CrB stars.